2016
DOI: 10.1016/j.ijid.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical metagenomic analysis of bacterial communities in breast abscesses of granulomatous mastitis

Abstract: This study profiled the microbiota of patients with GM and indicated an important role for Corynebacterium, and in particular C. kroppenstedtii, in the pathogenesis of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 21 publications
1
53
0
1
Order By: Relevance
“…The pathogens in patients with GLM have not yet been fully clarified. Previous studies have suggested that C. kroppenstedtii is the main pathogen of GLM (Yu et al, 2016;Fernández-Natal et al, 2016;Johnstone et al, 2017). In the present study, the initial data showed the presence of the C. kroppenstedtii sequence in 14 of the 40 patients (35%).…”
Section: Discussionsupporting
confidence: 57%
“…The pathogens in patients with GLM have not yet been fully clarified. Previous studies have suggested that C. kroppenstedtii is the main pathogen of GLM (Yu et al, 2016;Fernández-Natal et al, 2016;Johnstone et al, 2017). In the present study, the initial data showed the presence of the C. kroppenstedtii sequence in 14 of the 40 patients (35%).…”
Section: Discussionsupporting
confidence: 57%
“…All patients were managed conservatively with systemic antibiotics consisting of augmentin (1 mg twice a day) for 6 weeks and metronidazole (400 mg three times a day) for two weeks, and 17 out of 20 patients (85%) showed significant improvement. The difference in antibiotic efficacy between studies may be due to accidental or specific types of antibiotics used by [20,21]. Based on this consideration, in our treatment design, we used hydrogen peroxide, iodophor, and metronidazole to irrigate the lesions during and after surgery, and we achieved good results.…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly used for systemic or local infection caused by anaerobic bacteria, especially for Bacteroides, Clostridium, some Eubacteria, digestive cocci, and digestive Streptococcus. Some researchers believe that the occurrence of GLM is related to anaerobic bacteria, especially Corynebacterium [14,15].…”
Section: Discussionmentioning
confidence: 99%